Quality Evaluation of Spray-Dried Shell Protein Derived from Flower Tail Shrimp (Metapenaeus dobsoni) - Seethl, Lakshmi; A. Jeyakumari; U. Parvathy; A. A. Zynudheen (Fishery Technology, 2022)
During shrimp processing, large quantities of waste are generated in the form of head and carapace, which comprises a fair amount of biomolecules like chitin, protein, fat, minerals, astaxanthin, etc. The current practice for the utilization of shrimp waste is the extraction of chitin and chitosan. However, during production of chitin, protein present in the shells are not utilized properly and it can be recovered mechanically. In the present study, the shrimp shell protein was extracted from Metapenaeus dobsoni by mechanical process and spray dried. The proximate composition and chemical quality parameters (TVBN, TMAN, PV, FFA, and TBA) of Shrimp Shell, Shrimp Shell Protein Solution (SSPS), and Spray-dried Shrimp Shell Protein Powder (SSPP) were evaluated. Functional properties such as foaming capacity, Foam stability, Water absorption capacity, Oil absorption capacity, Hygroscopicity, and Flow properties of SSPP were also investigated. The TVBN, TMAN, PV, FFA, and TBA values of Shrimp Shell, SSPS, and SSPP were found to be within acceptable limits. Higher protein content was found in SSPP (64.27±0.56%) than in SSPS (52.35±1.04%), the result suggested that SSPP can be incorporated into food as a good source of protein for human consumption.